1990
DOI: 10.1051/lait:1990318
|View full text |Cite
|
Sign up to set email alerts
|

Caractéristiques rhéologiques et gélification thermique du concentré de protéines de lactosérum

Abstract: Résumé -Le comportement rhéologique et la cinétique de gélification thermique d'un concentré de protéines de lactosérum (CPL) diafiltré et délipidé ont été étudiés à partir d'un viscosimètre à cylindres coaxiaux. Les caractéristiques rhéologiques des gels ont été estimées avec un rhéomètre à compression. Les solutions du CPL, contenant de 4 à 14% de protéines, à 25 oC et à pH 7, présen-tent un comportement newtonien pour des vitesses de cisaillement comprises entre 82 et 955 S-l.Le logarithme de la viscosité e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Increasing pH increased the proportion of residues involved in calcium bridges. lt has been shown that the strength of thermal gels from clarified whey protein concentrates increased with pH increasing from 5 to 9 (Gault et al, 1990). At low pH, the gel strength was essentially explained by non-specifie interactions between protein molecules, while calcium bridges and disulphide bond formation explained gel strength at higher pH (Schmidt et al, 1979).…”
Section: Gelling Propertiesmentioning
confidence: 98%
“…Increasing pH increased the proportion of residues involved in calcium bridges. lt has been shown that the strength of thermal gels from clarified whey protein concentrates increased with pH increasing from 5 to 9 (Gault et al, 1990). At low pH, the gel strength was essentially explained by non-specifie interactions between protein molecules, while calcium bridges and disulphide bond formation explained gel strength at higher pH (Schmidt et al, 1979).…”
Section: Gelling Propertiesmentioning
confidence: 98%
“…IT IS EXTREMELY DIFFICULT to remove all residual lipids from whey protein products (Kilara, 1994). Investigators have successfully applied various pretreatments to produce whey protein concentrates with reduced lipid content and improved functional properties (Breslau et al, 1975;Fauquant et al, 1985;Gault et al, 1990;Grindstaff, 1975;Kim et al, 1989;Lehmann and Wasen, 1990;Marshall, 1982;Maubois et al, 1987;Rinn et al, 1990). However, no reports have been published on the effects of lipid class composition on functional properties of whey protein concentrates.…”
Section: Introductionmentioning
confidence: 99%